"No one would like to take a risk": Multilingual students' views on language mixing in academic writing. (November 2020) - Kafle, Madhav
Abstract: A significant number of studies have made advanced arguments for closing the gap between monolingual language and literacy pedagogy and multilingual classroom reality in higher education. Despite such theoretical advancement, studies that tap into views of the students on the very issue are just starting to appear. This study investigates perspectives of undergraduate international multilingual students on mixing languages in academic writing from a learner beliefs lens. All multilingual undergraduate students in a US university, my participants unhesitatingly mix languages in their daily communication. However, they believe that language mixing in formal writing is not a good choice because of four reasons. They see language mixing as: a. problem to the genre of academic writing itself; b. problem to the students themselves as their writing will be seen as deviant and assigned a low score; c. contradiction to the whole purpose of academic communication; and d. identity crisis to both people and languages. By highlighting emic views of the students, this study problematizes the arguments made by various theoretical studies.